Insights into T Cell Recognition of Antigen: Significance of Two-Dimensional Kinetic Parameters - Edwards, Lindsay J.; Zarnitsyna, Veronika I.; Hood, Jennifer D.; Evavold, Brian; Zhu, Cheng (Frontiers in Immunology, 2012)
The kinetic parameters governing T cell activation have been intensely studied for over a decade. However, the details of how the various aspects of receptor:ligand interactions culminate in T cell activation remains shrouded in mystery. Initial measurements were generated using surface plasmon resonance, a three-dimensional (3D) technique in which fluid-phase receptors and ligands are removed from their cellular environment. This approach demonstrated kinetics of TCR:pMHC interaction with relatively low affinities and slow off-rates for agonist peptides. Newer generation techniques have analyzed TCR:pMHC interactions in two dimensions (2D), with both proteins anchored in apposing plasma membranes. These approaches reveal TCR:pMHC interaction kinetics that are of high affinity and exhibit rapid off-rates upon interaction with agonist ligands. Importantly, 2D binding parameters correlate better with T cell functional responses to a spectrum of ligands than 3D measures.